2014
DOI: 10.1016/j.resconrec.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Use of recycled products in UK construction industry: An empirical investigation into critical impediments and strategies for improvement

Abstract: Construction industry consumes about half of all material resources taken from nature, and generates a large portion of waste to landfill. A way of tackling negative environmental impacts impending from continuous material extraction and waste generation is the use of recycled materials for construction projects. However, the use of recycled materials is yet to become a commonplace in construction industry. This study evaluates the factors hampering the use of recycled products in UK construction industry as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 58 publications
(53 reference statements)
3
86
0
Order By: Relevance
“…This is in agreement with earlier studies, which suggest that specification and subsequent use of recycled materials is indispensable to waste minimization and the overall global sustainability agenda (Oyedele et al, 2014). Based on this, there is need to procure secondary materials and support reuse of existing materials (Begum et al, 2009).…”
Section: Low Waste Materials Purchase Managementsupporting
confidence: 89%
See 2 more Smart Citations
“…This is in agreement with earlier studies, which suggest that specification and subsequent use of recycled materials is indispensable to waste minimization and the overall global sustainability agenda (Oyedele et al, 2014). Based on this, there is need to procure secondary materials and support reuse of existing materials (Begum et al, 2009).…”
Section: Low Waste Materials Purchase Managementsupporting
confidence: 89%
“…A study by the UK's Building Research Establishment (BRE, 2003) suggests that up to £130million gain could be made by reducing UK construction waste by only 5%. In order to harness this financial benefit and prevent impending environmental problems from waste generation (Oyedele et al, 2014), several research efforts have been made. This section evaluates the research streams in construction waste management.…”
Section: Construction Waste and Its Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As this means that the industry contributes the largest proportion of UK waste to landfill, similar patterns exist in other large economies . Construction activities in the US generates about 29% of landfill waste (Yu et al, 2013), while the industry landfills about 40%, 44%, 27% and 25% in Brazil, Australia, Canada and Hong Kong respectively (Lu and Tam, 2013;Oyedele et al, 2014). Albeit negative environmental impacts of waste, reducing construction waste could result in substantial financial gains.…”
Section: Introductionmentioning
confidence: 99%
“…3.2). As Oyedele et al (2014) found, one of the impediments to the use of recycled materials in the construction sector is that "Materials selection and specification are influenced by cost rather than environmental benefits". Indeed, the integration between economic, social and environmental aspects is needed (Yuan et al, 2011).…”
Section: Economic Domainmentioning
confidence: 99%